COMPARATIVE ANALYSIS OF CLOUD COGNITIVE SERVICE PROVIDERS BY USING COMPUTER VISION’S OBJECT DETECTION - Ivulis, Jāzeps; Štekels, Kārlis; Teilāns, Artis (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
The given paper’s “Comparative analysis of cloud cognitive service providers by using computer vision’s object detection” goal is to analyze prediction precision of objects in digital image, using different cognitive services what are available in the market. During the research process there were made a several trials using different computer vision services to analyze the same number of images. Every separate image was under detailed analysis for prediction accuracy of each object. The results show that there is significant difference between different vision services.